2023
DOI: 10.3390/ijms24076736
|View full text |Cite
|
Sign up to set email alerts
|

Interferons and Resistance Mechanisms in Tumors and Pathogen-Driven Diseases—Focus on the Major Histocompatibility Complex (MHC) Antigen Processing Pathway

Abstract: Interferons (IFNs), divided into type I, type II, and type III IFNs represent proteins that are secreted from cells in response to various stimuli and provide important information for understanding the evolution, structure, and function of the immune system, as well as the signaling pathways of other cytokines and their receptors. They exert comparable, but also distinct physiologic and pathophysiologic activities accompanied by pleiotropic effects, such as the modulation of host responses against bacterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 242 publications
0
2
0
Order By: Relevance
“…Impairment of antigen processing and presentation in DFUNH may result in clearance defects of pathogens and other antigens, leading to the sustained non-healing state of the wound. Interferon signaling plays an important regulatory role in antigen presentation and immune response by regulating the activation, maturation, and MHC molecule expression of APC cells, as well as directly affecting the functions of other immune cells [ 25 , 26 ]. Studies have shown that the absence of IFN-γ and IFN-κ impairs wound healing in diabetes wounds [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Impairment of antigen processing and presentation in DFUNH may result in clearance defects of pathogens and other antigens, leading to the sustained non-healing state of the wound. Interferon signaling plays an important regulatory role in antigen presentation and immune response by regulating the activation, maturation, and MHC molecule expression of APC cells, as well as directly affecting the functions of other immune cells [ 25 , 26 ]. Studies have shown that the absence of IFN-γ and IFN-κ impairs wound healing in diabetes wounds [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Ouyang et al highlighted that PRKAA2 facilitates immune escape in tumor cells by reducing CD8+ T cells and promoting the generation of regulatory T cells (Tregs), thereby contributing to tumor progression [68]. Moreover, malignant cells with high PRKAA2 expression evade immune suppression by losing major histocompatibility complex class I (MHC-I)-mediated interferongamma/Janus kinase/signal transducer and activator of transcription (IFN-γ/JAK/STAT) pathway molecules [69]. On the other hand, Varghese et al indicated that reduced PRKAA1 expression is a non-correlated prognostic factor in glioblastomas, highlighting the heterogeneity of the tumor cells, which probably influences the results obtained [70].…”
Section: Discussionmentioning
confidence: 99%